Susceptibility to CD8 T cell-mediated killing influences the reservoir of latently HIV-1 infected CD4 T cells - Buzon, Maria J. (2014)
BACKGROUND: HIV-1 establishes a life-long infection in the human body, but host factors that influence viral persistence remain poorly understood. Cell-intrinsic characteristics of CD4 T cells, the main target cells for HIV-1, may impact the composition of the latent viral reservoir by altering the susceptibility to CD8 T cell mediated killing. RESULTS: We observed that susceptibilities of CD4 T cells to CD8 T cell-mediated killing, as determined in direct ex-vivo assays, were significantly higher in persons with natural control of HIV-1 (elite controllers) than in individuals effectively treated with antiretroviral therapy. These differences were most pronounced in naïve and in terminally-differentiated CD4 T cells, and corresponded to a reduced viral reservoir size in elite controllers. Interestingly, the highest susceptibility to CD8 T cell-mediated killing and lowest reservoirs of cell-associated HIV-1 DNA was consistently observed in elite controllers expressing the protective HLA class I allele B57. CONCLUSION: These data suggest that the functional responsiveness of host CD4 T cells to cytotoxic effects of HIV-1-specific CD8 T cells can contribute to shaping the structure and composition of the latently infected CD4 T cell pool.